Insights Into Food Buying Decision - Maricica Stoica; Dimitrie Stoica; Cezar Ionut Bichescu (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
This study aims to investigate the process of consumer purchasing decisions for food products, focusing on the roles of price, emotion, packaging, and labeling. Consumer decisions involve recognizing a need, seeking information, evaluating alternatives, making the purchase, and post-purchase evaluation. Key stages like information search and mental evaluation are critical, as consumers utilize various sources to assess products based on price, quality, and brand reputation. Price influences emotions and purchasing intentions, with positive perceptions encouraging purchases and negative ones deterring them. Packaging significantly affects decision-making, particularly for low-involvement purchases, by evoking strong emotional responses through elements like colors and images. Food labels, serving as essential communication tools, affect consumer perceptions and decisions, with health and hedonistic labels influencing skepticism and evaluation. Effective marketing strategies that address both cognitive and emotional aspects of consumer behavior can enhance decision-making, reduce post-purchase dissonance, and foster long-term satisfaction and loyalty.